STUDY ON TECHNOLOGICAL GAP ANALYSIS AND GARRETT RANKING IN RECOMMENDED PEST MANAGEMENT PRACTICES RANKING IN RECOMMENDED PEST MANAGEMENT PRACTICES OF TEMPERATE FRUIT CROPS AT KODAIKANAL HILLS ANAL HILLS, TAMIL NADU - K.ELANGO; I. MUTHUVEL (The Bioscan, 2019)
Agriculture is the mainstay of the Indian economy, contributing over 17 per cent to the total GDP and Creating employment to over 60 per cent of the population. A study was conducted on technological gap in adoption of IPM pest management practices in Kodaikanal taluk of Dindigul district in Tamil Nadu with 60 respondents from Vadakavunji and Senbaganoor villages through simple random sampling during March – May 2020.To identify a best package practice of the technology, the finalized nine practices were resistant variety, Seed treatment, Yellow sticky traps, Light traps, Predators, Parasitoids, Entomopathogen, Botanicals and Chemical insecticides. The findings revealed that among the practices 96.67 per cent farmers adopting chemical treatment it means spraying insecticides to controlling the pests followed by Botanicals (86.67 per cent). The gap was 86.67 per cent in predators and 95.00 per cent in parasitism. From the ranking of the pest management practices spraying of chemical for controlling pests takes up the first position followed by yellow sticky trap and botanicals. Further, lack of knowledge, lack of technical help, unconvincing merit of technology and non-availability of technical inputs complexity of practices were expressed as reasons for t--echnological gap in adoption of pest management practices in temperate fruit crops.